Duplication 9p due to unequal sister chromatid exchange. Issue 5 (May 1987) - Mattina, T; Sorge, G; Milone, G; Garozzo, R; Conti, L
Abstract : A case of trisomy 9p syndrome is reported. The karyotype showed a tandem duplication of the short arm and of the inverted heterochromatic block of chromosome 9. Unequal sister chromatid exchange seems to be the only possible cause of this finding.